Pandemic and Education - Buda, András; Czékmán, Balázs (Central European Journal of Educational Research, 2021)
The emergence and rapid spread of the Coronavirus in the spring of 2020 has fundamentally changed our lives. The most important change has been the attempt to minimise face–to–face contacts everywhere in order to keep the epidemic under control. Public gatherings were banned, shopping malls were closed, and sporting events were also cancelled. As COVID–19 spread as easily among children as among adults, schools could not escape the restrictions. During the first wave of the epidemic, institutions had to switch to emergency remote education (ERE) at very short notice, which presented a number of problems for all participants. These problems and experiences of the switch should be collected at all levels of education, as they not only help to prepare for similar situations, but may also lead to conclusions that can be used to make the methods and solutions of classroom–based teaching more motivating, more effective or even more efficient. In this paper, we review both the challenges of the transition and the possible implications for the future teaching–learning process by reflecting on the lessons learned.